2019
DOI: 10.1177/0741088319880511
|View full text |Cite
|
Sign up to set email alerts
|

Examining African American Girls’ Literate Intersectional Identities Through Journal Entries and Discussions About STEM

Abstract: This article examines how three African American girls, ages 10 to 18, used journaling and interviews to better understand science, technology, engineering, and mathematics (STEM) as part of their literate identities. Drawing on prior work about literate identities, the authors introduce the concept of literate intersectional identities, which describes how participants’ diverse histories, literacies, and identities traverse categories, communities, genres, and modes of meaning within the context of a STEAM wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 43 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…In considering the disproportionate racial and gender representation in STEM disciplines, scholars have considered the educational climates many students matriculate through as a potential source of inequity. Previous findings have shown that students are aware of racial and gender disparities in STEM and often attribute these inequities to racism and discrimination (Hanson, 2009;Lewis Ellison et al, 2020). For instance, Ikkatai et al (2020) found that 61% of the high-school, undergraduates, and graduate students they surveyed reported experiencing gender bias in their math or science classes from peers or teachers.…”
Section: High-school Students and Experiences With Science And Stemmentioning
confidence: 98%
See 2 more Smart Citations
“…In considering the disproportionate racial and gender representation in STEM disciplines, scholars have considered the educational climates many students matriculate through as a potential source of inequity. Previous findings have shown that students are aware of racial and gender disparities in STEM and often attribute these inequities to racism and discrimination (Hanson, 2009;Lewis Ellison et al, 2020). For instance, Ikkatai et al (2020) found that 61% of the high-school, undergraduates, and graduate students they surveyed reported experiencing gender bias in their math or science classes from peers or teachers.…”
Section: High-school Students and Experiences With Science And Stemmentioning
confidence: 98%
“…In contrast, some in and out-of-school STEM programming centers the perspectives of Black girls (Archer et al, 2021;King, 2017;Lewis Ellison et al, 2020) and Indigenous students (Miller & Roehrig, 2018). Out-of-school learning shows particular promise when science is positioned as "mattering" by addressing community problems, what Birmingham et al (2017) refer to as "consequential learning."…”
Section: Strategies To Expand Representation and Mitigate Exclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study explored a literacy collaborative in which girls wrote poetry expressing their identities and used writing to question, challenge, and change dominant discourses in society (Muhammad, 2015). Lewis Ellison, Robinson, and Qiu (2020) looked at three girls' STEM journal writings and uncovered intersecting themes of race, gender, power, and privilege in STEM. Within pedagogies such as these, students draw on their socially and culturally rooted identities, family, and community (Hall, 2007).…”
Section: The Writing Of African American Adolescentsmentioning
confidence: 99%
“…In a STEM summer workshop for girls, Lewis Ellison et al (2020) studied three African American girls’ journal writing and intersectional identities. Through discussion and journaling, the girls expressed their identities as Black girls interested in STEM.…”
Section: Black Youth Writing Programsmentioning
confidence: 99%